L'éthique environnementale dans les outils d'évaluation économique et environnementale : application à l'équité intergénérationnelle et à la gestion des déchets - Jacques Méry (VertigO, 2010)
Equity between generations is at the heart of the sustainability concept. But the economic and environmental evaluation tools for public decision aid rarely make their assessments explicit relative to environmental ethics, especially about temporality : which choices for temporal preferences (temporal horizons, possible preferences for the present) and how are irreversibilities taken into account ? An analysis of the hypotheses concerning temporality is proposed here for life-cycle analyses, the ecological footprint and economic valuations (cost-benefit analyses). These hypotheses can indeed induce very different results when comparing scenarios. It is then important to be the most possible transparent about them, all the more since a trend is sometimes seen to show these tools as neutral, objective, or impartial while they have hidden values. Therefore, their disputable character, including by lay people, is not removed as a matter of course. Applications to waste management are shown focusing on the problematics of landfilling. The valuation of externalities are made using the discounting procedure due to E. Kula, linking the short run of individuals and the long run of societies and complying by design with intergenerational equity.